2022
DOI: 10.1073/pnas.2122486119
|View full text |Cite
|
Sign up to set email alerts
|

The impact of paleoclimatic changes on body size evolution in marine fishes

Abstract: Body size is an important species trait, correlating with life span, fecundity, and other ecological factors. Over Earth’s geological history, climate shifts have occurred, potentially shaping body size evolution in many clades. General rules attempting to summarize body size evolution include Bergmann’s rule, which states that species reach larger sizes in cooler environments and smaller sizes in warmer environments, and Cope’s rule, which poses that lineages tend to increase in size over evolutionary time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 74 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…Because time spent growing is one of the primary determinants of body size (Dmitriew, 2011), the very presence of MHC‐based adaptive immunity could drive the evolution of body size. Such a mechanism could be one of the drivers of the macroevolutionary trend of an increase in body size over evolutionary timescales (Cope's rule), which is particularly well supported by data from marine vertebrates (Heim et al, 2015; Smith et al, 2016; Troyer et al, 2022).…”
Section: Introductionmentioning
confidence: 73%
“…Because time spent growing is one of the primary determinants of body size (Dmitriew, 2011), the very presence of MHC‐based adaptive immunity could drive the evolution of body size. Such a mechanism could be one of the drivers of the macroevolutionary trend of an increase in body size over evolutionary timescales (Cope's rule), which is particularly well supported by data from marine vertebrates (Heim et al, 2015; Smith et al, 2016; Troyer et al, 2022).…”
Section: Introductionmentioning
confidence: 73%
“…In light of this, it is somewhat surprising that intra‐ and interspecific size gradients were largely congruent in a study of various Drosophila species, with larger species found at higher latitudes (Rohner et al, 2018). This shows that in at least some taxa, there is some congruence between intra‐ and interspecific latitudinal size gradients, perhaps reflecting a common and shared body size response to lower temperatures at higher latitudes (Rohner et al, 2018; Troyer et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…In summary, mean body size of tortoises has not exhibited marked fluctuations over 23 Ma, but large and rapid changes have resulted in a smaller mean body size and shifted body size distribution patterns in extant tortoises relative to their fossil counterparts. Phylogenetic analysis has provided refined insights into body size evolution across vertebrates [55][56][57][58][59][60]. However, we excluded phylogenetic comparative methods from our approach for two reasons.…”
Section: Discussionmentioning
confidence: 99%